Testing Water Harvesting from Dew and Fog as Additional Source of Freshwater in Some Areas inside Syria - قره علي أحمد; أسعد محمد; خليل مجد (Latakia University Journal -Biological Sciences Series, 2021)
Due to climate change and reduced surface drinking water levels, stress on traditional water sources in Syria has recently risen. Therefore, there is an urgent need to move toward non-traditional sources, including air humidity. since atmospheric water harvesting is renewable and sustainable. In this study, the mechanism for collecting water using traditional fog and dew collection tools is presented, along with the chemical treatment of these tools. Two prototypes of networks to collect water from atmospheric air have been designed and built. The prototypes were distributed in a geographical sequence extending from coastal to central regions to the eastern region. In order to be tested in different climatic conditions. The humid coastal areas showed water collection rates (non-rainfall) ranging from 0.3-1.4 liter/m2/day. While the moderate aridity region recorded rates ranged between 0.2-0.8 liter/m2/day. While the dry eastern region recorded the lowest rates between 0-0.4 liter/m2/day. The results of the chemical analyses of the rain water samples collected were consistent with the specifications of the Syrian standard and WHO drinking water standards.